18F-sodium fluoride bone deposition quantitation with PET in Mice: Variation with age, sex, and circadian rhythm - Dorau-Rutke, Viktoria; Huang, Kai; Lukas, Mathias; Schulze, Marc O.; Rosner, Christian; Gregor-Mamoudou, Betina; Steffen, Ingo G.; Brenner, Winfried; Beindorff, Nicola (Nuklearmedizin - NuclearMedicine, 2020)
Aim The aim of this study was to establish a data base for normal 18F-sodium fluoride (18F-NaF) bone uptake as a function of age, sex and circadian rhythm in mice.Methods In 12 female (F) and 12 male (M) C57BL/6N mice PET images were acquired 90 min after intravenous injection of 20 MBq 18F-NaF for 30 minutes. Each mouse was imaged in follow-up studies at 1, 3, 6, 13 and 21 months of age. In order to assess for physiologic changes related to circadian rhythm, animals were imaged during light (sleep phase) as well as during night conditions (awake phase). Bone uptake is described as the median percentage of the injected activity (%IA) and in relation to bone volume (%IA/ml).Results A significant smaller bone volume was found in F (1.79 ml) compared to M (1.99 ml; p < 0.001). In sex-pooled data, highest bone uptake occurred at an age of 1 month (61.1 %IA, 44.5 %IA/ml) with a significant reduction (p < 0.001) at age 3 months (43.6 %IA, 23.6 %IA/ml), followed by an increase between 13 (47.3 %IA, 24.5 %IA/ml) and 21 months (52.2 %IA, 28.1 %IA/ml). F had a significantly higher total uptake (F 48.2 %IA, M 43.8 %IA; p = 0.026) as well as a higher uptake per ml bone tissue (F 27.0 %IA/ml; M 22.4 %IA/ml; p < 0.001). A significant impact of circadian rhythm was only found for F at ages of 3 and 6 months with a higher uptake during the sleep phase.Conclusion Circadian rhythm had a significant impact on uptake only in F of 3 and 6 months. Regarding sex, F showed generally higher uptake rates than M. The highest uptake values were observed during bone growth at age 1 month in both sexes, a second uptake peak occurred in elderly F. Designing future bone uptake studies with M, attention must be paid to age only, while in F circadian rhythm and age must be taken into account.
Keywords: bone; 18F-fluoride; PET; sex; circadian rhythm; age; mouse